Neotypification and identity of the name Clematis jinzhaiensis (Ranunculaceae) - Li, Jin-Yu; Liao, Shuai; Li, Liang-Qian; Xie, Lei (Phytotaxa, 2015)
Clematis jinzhaiensis Xue & Wang (1986: 406) was described on the basis of a single collection from Jinzhai of Anhui Province in China. According to the protologue, the type specimen was collected by Z. W. Xue (No. 21) on 20 September 1982, which was deposited at the herbarium of the Institute of Biology (AIB) in Hefei, Anhui. After C. jinzhaiensis was published, however, researchers have failed to access this specimen at AIB. During the taxonomic revision of Clematis Linnaeus (1753: 543) sect. Campanella Tamura (1987: 38), we made it clear that the type was kept and finally lost by the authors (Xie 2005; Fig. 1b), so the type material was never deposited at AIB.